2011
DOI: 10.1016/j.ajpath.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis Reveals cAMP-Dependent Enhancement of Microvascular Endothelial Barrier Functions via Rac1-Mediated Reorganization of Intercellular Junctions

Abstract: The barrier between blood and the surrounding interstitium, limiting the exchange of fluid and solutes, is provided by a single layer of endothelial cells that are coupled by intercellular junctions. Various pathological conditions in humans, such as edema, hemorrhagic stroke, and vascular malformations, have been, at least in part, caused by impaired endothelial barrier function and disruption of cell junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…37 Notably, the only treatments shown to reduce the frequency and severity of SCLS attacks, aside from IVIG, is a regimen of theophylline (phosphodiesterase inhibitor) and terbutaline (␤-adrenergic agonist), 6,38 which are known to promote endothelial barrier function by stabilizing VE-cadherin-mediated adhesive junctions. [39][40][41] Thus, our results could account for the effectiveness of these therapies for SCLS.…”
Section: Discussionmentioning
confidence: 99%
“…37 Notably, the only treatments shown to reduce the frequency and severity of SCLS attacks, aside from IVIG, is a regimen of theophylline (phosphodiesterase inhibitor) and terbutaline (␤-adrenergic agonist), 6,38 which are known to promote endothelial barrier function by stabilizing VE-cadherin-mediated adhesive junctions. [39][40][41] Thus, our results could account for the effectiveness of these therapies for SCLS.…”
Section: Discussionmentioning
confidence: 99%
“…Under resting conditions, these enzymes stabilize the circumferential actin fibers that support robust VE-cadherin adhesions. Activation of Rac1 or Cdc42 have been noted downstream of S1P 7 and cAMP/Rap1 signaling, 8,9 both of which are known to stabilize endothelial cell junctions.…”
Section: Regulation Of Inter-endothelial Adherens Junctions Under Resmentioning
confidence: 98%
“…Furthermore, there are also clear differences in the behavior toward macromolecules, such as low-density lipoproteins (LDLs), between brain endothelial cells and peripheral endothelium (Dehouck et al, 1994). Spindler et al (2011) indicated that cAMP signaling is barrier-protective via Rac1 in microvascular endothelial cells, but not in macrovascular endothelial cells. Our observation may represent an intrinsic difference between brain and peripheral endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that HGF induced F-actin rearrangement and increased the expression of VE-cadherin in RBEC. The rearrangement of cytoskeletal actin fibers is an important factor that affects barrier function of endothelial cells (Lai et al, 2005;Vandenbroucke et al, 2008;Spindler et al, 2011). Accumulating evidence suggests that HGF stimulates multiple signaling pathways, such as small GTPase Rac, MAP, PKC, PI3-kinase, and its downstream effector GSK-3β (Liu et al, 2002;Trusolino et al, 2010).…”
Section: Discussionmentioning
confidence: 99%